Comparison between Tonifying Kidney Yang and Yin in Treating Segmental Bone Defects Based on the Induced Membrane Technique: An Experimental Study in a Rat Model. (28th December 2020) - Shen, Zhen; Chen, Zehua; Shi, Xiaodong; Wang, Tao; Huang, Minling; Chen, Guoqian; Ye, Xiangling; Hou, Chengzhi; Liu, Wengang; Dong, Wei; Guo, Ying
Abstract : Tonifying kidney therapy consisting of tonifying kidney yang and yin is the basic principle of Chinese medicine in treating segmental bone defects (SBDs). Previous studies have demonstrated the presence of the differences between tonifying kidney yang and yin in bone metabolism of osteoporosis and distraction osteogenesis models. However, whether the difference between the two tonifying kidney methods in bone repair for the induced membrane (IM) technique occurs or what is the difference remain unclear. Angiogeneic-osteogenic coupling plays an important role in bone repair and the induced membrane couples angiogenesis with the later osteogenesis during the IM process. This study aimed at investigating the effects of tonifying kidney yang (total flavonoids of Rhizoma Drynariae, TFRD) and yin (plastrum testudinis extract, PTE) on angiogenesis and osteogenesis in the IM-treated SBDs. Rats of 6 mm tibia bone defect model treated with IM were divided into five groups: the control group, the model group, the tonifying kidney yang group (TFRD-treated group), the tonifying kidney yin group (PTE-treated group), and the western medicine group. At 4 weeks after insertion of the polymethylmethacrylate (PMMA), three caudal vertebrae from the tail in each rat were implanted into the 6 mm defect gap. Radiographical, histological, immunohistochemical, and immunofluorescent analyses were performed to assess bone and vessel formation at 4 or 12 weeks after insertion of the PMMA, respectively. Our results revealed that TFRD and PTE were beneficial to both angiogenesis and osteogenesis. TFRD exerted a better effect on angiogenesis than PTE and achieved a better result in stage 1 rather than in stage 2 of IM, whereas PTE was superior to TFRD in osteogenesis and achieved a better result in stage 2 instead of stage 1. Collectively, these findings elucidated the beneficial effects of tonifying kidney yang and yin on angiogenesis and osteogenesis of SBD repair during the IM process, as well as the difference that tonifying kidney yang surpasses tonifying kidney yin in angiogenesis while tonifying kidney yin outperforms tonifying kidney yang in osteogenesis, which suggests that the combination between the application of tonifying kidney yang method in stage 1 of IM and tonifying kidney yin method in stage 2 may achieve better repair efficiency.